Systemic and local myotoxicity induced by snake venom group II phospholipases A2: Comparison between crotoxin, crotoxin B and a Lys49 PLA2 homologue - Gutiérrez, José María (2008)
The patterns of myotoxicity induced in mice by crotoxin, crotoxin B and a Lys49 phospholipase A2 (PLA2) homologue were compared. Lys49 PLA2-induced local myotoxicity is reflected by creatine kinase (CK) loss in injected gastrocnemius muscle, and by a profile of CK increase in plasma characterized by a rapid increment and drop after intramuscular injection, and by a lack of CK increase in plasma after intravenous injection. In contrast, crotoxin and crotoxin B, which induce local and systemic myotoxicity, provoked a more prolonged increment in plasma CK activity upon intramuscular injection, and induced increments in plasma CK after intravenous injection. The three toxins promoted a similar extent of local myotoxicity, assessed by the loss of CK in injected gastrocnemius. A method for the quantitative assessment of the ability of toxins to induce systemic myotoxicity is proposed, based on the estimation of the ratio between the area under the curve in the plasma CK activity (total myotoxicity) to the loss of CK in injected gastrocnemius (local myotoxicity). The highest ratio corresponded to crotoxin, and the lowest corresponded to Lys49 PLA2, the former being a systemic myotoxin and the latter a local myotoxin. Neutralization by antivenoms also differed between the toxins: a drastic reduction in plasma CK, with very poor neutralization of local CK loss, was achieved in the case of crotoxin B when antivenom was injected intravenously, whereas no neutralization was achieved in the case of Lys49 PLA2. When tested in undifferentiated myoblasts in culture, Lys49 PLA2 induced cytotoxicity, whereas crotoxin and crotoxin B did not, evidencing that the latter are devoid of widespread cytolytic activity. Molecular modeling analysis showed that Lys49 PLA2 has a conspicuous cationic face, which is likely to interact with diverse membranes. In contrast, crotoxin B, despite its overall basic pI, has a lower density of positively charged residues at this molecular region. It is suggested that Lys49 PLA2s homologues interact, through this cationic face, with many different cell types, thus lacking specificity for muscle cells. In contrast, crotoxin B has a more selective interaction with targets in the muscle cell membrane. This selectivity might be the basis for the ability of crotoxin and crotoxin B to induce systemic myotoxicity.